Reactivity Descriptors for Iron Porphyrins and Iron Phthalocyanines as Catalysts for the Electrooxidation of Reduced Glutathione - Paez-Collio, M; Paez-Collio, M; Zagal-Moya, J; Zagal-Moya, J; Gutierrez-Ceron, C; Gutierrez-Ceron, C (Springer New York LLC, 2016)
We have examined the electrocatalytic activity for the oxidation of glutathione of a wide variety of molecular catalysts: FeN4 complexes (MN4 = metal porphyrins and metal phthalocyanines) confined on the surface of graphite electrodes in order to establish reactivity descriptors for these catalysts for this reaction. We have conducted these studies mainly in alkaline media (pH = 13). The reaction order in OH− is 1 for pH values lower than 8. For higher pH values, the reaction becomes pH independent. The reaction order in glutathione is close to 1 in the concentration range examined (10−3–10−2 M). The activity of the surface-confined MN4 complexes is related to the Fe(II)/(I) and the Fe(III)/(II) redox transitions of the immobilized FeN4 complexes. The catalysts are active only in the potential range where the Fe(II) state predominates. The activity as (log j)E versus the Fe(II)/(I) formal potential varies in a non-linear fashion giving a volcano correlation as previously observed for the oxidation of L-cysteine and many other reactions catalyzed by MN4 complexes. A plot of (E)logj versus the Fe(II)/(I) formal potential gives also an asymmetrical volcano, with one of the branches with a slope close to unity. These volcano correlations clearly shows that the Fe(II)/(I) redox potential needs to be tuned to a certain potential to obtain a maximum activity for the oxidation of glutathione. Most Fe porphyrins show low activity because the metal center Fe(III) is in the wrong oxidation state in the potential range studied. © 2016, Springer-Verlag Berlin Heidelberg.